2000
DOI: 10.1128/jb.182.1.155-163.2000
|View full text |Cite
|
Sign up to set email alerts
|

Genetics of l -Sorbose Transport and Metabolism in Lactobacillus casei

Abstract: Genes encoding L-sorbose metabolism of Lactobacillus casei ATCC 393 have been identified on a 6.8-kb chromosomal DNA fragment. Sequence analysis revealed seven complete genes and a partial open reading frame transcribed as two units. The deduced amino acid sequences of the first transcriptional unit (sorRE) showed high similarity to the transcriptional regulator and the L-sorbose-1-phosphate reductase of the sorbose (sor) operon from Klebsiella pneumoniae. The other genes are transcribed as one unit (sorFABCDG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
68
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(70 citation statements)
references
References 49 publications
2
68
0
Order By: Relevance
“…The analysis of a spontaneous 2-DG-resistant mutant (BL30) lacking glucose-specific PTS activity provided the first evidence that the PTS in L. casei is involved in the CCR effect exerted by glucose on the utilization of lactose, ribose and sorbose (Veyrat et al, 1994;Yebra et al, 2000). It has been shown here that the phenotype of this strain is most likely due to a mutation in the IIAB Man protein encoded by manL.…”
Section: Discussionmentioning
confidence: 78%
See 3 more Smart Citations
“…The analysis of a spontaneous 2-DG-resistant mutant (BL30) lacking glucose-specific PTS activity provided the first evidence that the PTS in L. casei is involved in the CCR effect exerted by glucose on the utilization of lactose, ribose and sorbose (Veyrat et al, 1994;Yebra et al, 2000). It has been shown here that the phenotype of this strain is most likely due to a mutation in the IIAB Man protein encoded by manL.…”
Section: Discussionmentioning
confidence: 78%
“…Previous studies had shown that glucose uptake by the PTS is involved in the regulation of the ribose, lactose and sorbose catabolic pathways in L. casei (Veyrat et al, 1994;Yebra et al, 2000). In order to identify the genes encoding the PTS Man in L. casei, a search for genes encoding putative IID proteins was performed in the draft genomic sequence of L. casei BL23 (Klaenhammer et al, 2002).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, besides the nisin system, these approaches could not be transferred to species of Lactobacillus. In lactobacilli, the regulation of gene expression has been studied mainly for carbon catabolism pathways, such as those of lactose, xylose, ribose, sorbose, and arginine deiminase (1,2,3,10,18,19,30,34,35,43,49,50). In Lactobacillus casei, the best-characterized sugar transport is the lactose-specific phosphoenolpyruvate-dependent phosphotransferase system (PTS).…”
mentioning
confidence: 99%